PENERAPAN GAYA EKSPOSITORI PADA FILM DOKUMENTER COSMIC ENERGY I KETUT BUDIANA - Suardewanti, Ni Kadek Asri; Puriartha, I Kadek; Putra, Ida Bagus Hari Kayana (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
Documentary films are a development according to non-fiction films where documentary films contain information & contain the subjectivity of the makers. This means that what is recorded is based on existing facts (Nugroho, 2007). According to Chandra Tansil (2010:5), the stages of making a documentary film are divided into six parts, namely Building ideas, Research, Composing a storyline, Composing production design, Filming, Editing images and sound on the editing table. Expository Documentary Films or Documentaries that focus on presenting facts and information with clear and objective narratives. Expository documentaries are one type of documentary film that aims to convey information, facts, or knowledge to the audience objectively and informatively. The production of the documentary film